Inflammation and depression in young people: a systematic review and proposed inflammatory pathways - Toenders, Yara J; Laskaris, Liliana; Davey, Christopher G; Berk, Michael; Milaneschi, Yuri; Lamers, Femke; Penninx, Brenda W J H; Schmaal, Lianne (Molecular psychiatry, 2022)
Depression onset peaks during adolescence and young adulthood. Current treatments are only moderately effective, driving the search for novel pathophysiological mechanisms underlying youth depression. Inflammatory dysregulation has been shown in adults with depression, however, less is known about inflammation in youth depression. This systematic review identified 109 studies examining the association between inflammation and youth depression and showed subtle evidence for inflammatory dysregulation in youth depression. Longitudinal studies support the bidirectional association between inflammation and depression in youth. We hypothesise multiple inflammatory pathways contributing to depression. More research is needed on anti-inflammatory treatments, potentially tailored to individual symptom profiles.